Where Sun Meets Water : Floating Solar Market Report - World Bank Group; Energy Sector Management Assistance Program; Solar Energy Research Institute of Singapore (World Bank, Washington, DC, 2019)
Floating solar photovoltaic installations open new opportunities for scaling up solar generating capacity, especially in countries with high population density and competing uses for available land. Advantages of floating solar over land-based systems include higher energy yield, reduced evaporation, and improved water quality, among others. Combining floating solar with hydropower plants is of particular interest. Flexible hydropower output can be used to smooth the variability of the solar generation, while making better use of existing transmission assets, particularly beneficial in countries with weak grids. With a global estimated potential of 400 gigawatts, under conservative assumptions, floating solar could double the current global installed capacity of solar PV. Although the market is still nascent and challenges in deployment remain, the floating solar market is set to accelerate as the technologies mature. Floating Solar Market Report presents an overview of floating solar technologies, current deployment market and future opportunities, challenges related to floating solar deployment, policies and regulatory considerations, and current costs and project structuring. Floating Solar Market Report is the second publication of the series Where Sun Meets Water dedicated to floating and hydro-connected solar deployment.